Comprehensive review of opportunities and challenges of ethnomedicinal plants for managing type 2 diabetes - Valizadeh Lakeh Mahmoud; Ramtin Shayesteh; Trisha Krishni Foong Yun Loh; Sook Wah Chan; Gautam Sethi; Kevin Burgess; Sau Har Lee; Won Fen Wong; Chung Yeng Looi (Heliyon)
Diabetes mellitus is a prevalent metabolic disorder worldwide. A variety of antidiabetic medications have been developed to help manage blood glucose levels in diabetic patients, but adverse reactions and efficacy loss over time have spurred research into new therapeutic agents. In view of this, investigations into the antidiabetic effect of herbal products have been encouraged due to their potential availability, inexpensiveness, and relatively minimal side effects. This review explores the antidiabetic potentials of the eight most promising medicinal plants in terms of molecular mechanisms, phytochemistry, toxicology, and efficacy. These plant extracts have gone through clinical trials and demonstrated good control of blood glucose levels by increasing serum insulin levels, enhancing tissue glucose uptake, and/or decreasing intestinal glucose uptake. Yet, medicinal plants are far from being able to replace conventional antidiabetic drugs for patient management but they have the potential for further development if rigorous clinical trials on their mechanisms, delivery, and dose regimen are performed. To date, no study has been performed to isolate and characterize active compounds in these plant extracts, suggesting that further investigations in this area would be the next step to advance this field.